Code of conduct for industrial harmony: a new dimension & constructive approach towards better industrial relations / Maj Zulkiflee Mazlan - Mazlan, Maj Zulkiflee (Faculty of Law, 1987)
A registered company i.e . a company incorporated by registration under the companies Acts, is regarded by the law as a person, just as a human being. This artificial or Juvistic person can own land and other property, enter into contracts, sue and be sued, have a bank account in its own name, owe money to others and be a creditor of other people and other companies* and employ people to work for it * The company's money and property belong to the company and not to the members or shareholders, although the numbers or shareholders may be said to won the company similarly , the company's debts are the debts of the company and the shareholders cannot be compelled to pay them, although if , for example, the company is being wound up and its assets do not realise a sum sufficient to pay its debts, a shareholder whose liability is limited by shares is liable to contribute to the assets up to the amount, if any unpaid on his shares. A Company, of course, can only act through human agents, and those who manage its business are called directors . But the directors are only agents of the company, with the powers of management given by the company's a r tic le s of association and usually with power to delegate any of their powers to a managing director. The company is also liable for torts and crimes committed by its servants and agents within the scope of their employment or authority . This conception of a company as a corporation, i . e . a person separate and district from the other persons who are its members and directors , is the fundamental principle of company law.